Intermediation Under Trade Restrictions - Winkler, G. Michael (Quarterly Journal of Economics, 1989)
Intermediation is the activity of buying and selling simultaneously in one market. In this paper intermediation in the market for an arbitrary good is derived from trade restrictions in a general equilibrium exchange model. The trade restrictions are given by a trade feasibility relation defined on the set of households, and they necessitate dropping the one price assumption of standard general equilibrium theory. It is shown that in this setting equilibria need not exist in spite of well-behaved preferences and fully flexible prices. As a special case a simple economy with a linear market structure is analyzed in detail.